Teknik Job Order Costing dalam Perhitungan Harga Pokok Produksi pada UD. Nirwana - Diana, Khori Nur; Setyowati, Lis; Zulkarnain, Muhammad Afiq (Lembaga Publikasi Ilmiah Nusantara, 2023)
Purpose of this study was to determine the accuracy of the cost of goods produced at UD. Nirwana Furniture. This research uses a qualitative method with a comparative descriptive approach. Data collection in this study uses the results of interviews and observations. The analysis is carried out by calculating the cost of production at the company. The results showed that the company did not fully understand the job order costing method. There is a discrepancy between the calculation of cost of production according the company and according to the job order costing method. This is due to differences in the concepts of calculating factory overhead costs, so that the resulting calculation using the job order costing method is higher than according the company.